PENERAPAN SISTEM PEREKONOMIAN ISLAM (PENDEKATAN NORMATIF) - Hj. Hamsidar (AL-IQTISHAD, 2020)
AbstractThe implementation of islamic economic sistem a set of common foundations pf economy stipulated in the quran and al-sunnah, builton that foundation according to each environment and time. Al-quran and Sunnah as a source of islamic law plays an important role in providing the basics on the economic sistem in Islam. The main principles of islam presented are in accordance with the intent of human economic sistem according to the economy, the economic characteristics of islam and freedom of economic use according to Islam. Al-quran and sunnah, as norms, also mentioned problems related to the factors of production, working according to Islam, property  rghts in islamic view, contract and propertyutilization. Thus, is can be understood that islamic concept of economic activities does not only aim to earthly life alone but is also intended for the afterlife.Kata kunci: Penerapan; Ekonomi Islam; Pendekatan Normatif.